Interfaces rodoviário-urbanas na produção da cidade: estudo de caso do contorno rodoviário de João Pessoa-PB - Castro, Alexandre Augusto Bezerra da Cunha (2014)
Roads performed an important role in the design process of city, by facilitating long distance journeys. When necessary, contours were constructed that supposedly facilitate connectivity between the city and the highway. However, when absorbed into the urban fabric of cities, these stretches of road contours develop individual dynamics with intra-urban space in which it is inserted, with the change of accessibility, morphology and the use and occupation of urban land. These interfaces occur during the growth process of the city and during the subsequent stages. Within this context, this master's research aims to analyze the dynamics between the implementation of BR-230 road contour and the process of production of the urban space of the city of João Pessoa, Paraíba, between the years 1963 and 2013, in terms of morphology, use and occupation of urban land. To this end, we employed the method of evolutionary logic of the urban fabric of Panerai, which divides the urban evolution in three stages: overcoming limits, growth and combination and conflict. The method was associated with analytical tools such as Space Syntax and the use of Geographic Information System software. The results show that the highway boosted the process of spreading the city to the south, which produced a sprawling urban area, this being the fastest growing sector in that period, where they were also able to identify the pattern of horizontal and fragmented spatial growth, changes in accessibility based on morphology and pattern of use and occupation of spaces bordering the highway